Problem-based learning and digital platforms in medical education - Greenspan, Amanda A.; Goldberg, Gary S.; Hamilton, Kelly L. (Frontiers in Education, 2025)
Problem based learning (PBL) is based on the idea that learning is “grounded by experience. ” PBL curriculums in medical school highlight the importance of engaging students and allowing students to be the driver of their education. This mimics their work in the hospital where answers are rarely suited to a multiple-choice question, but a myriad of complex clinical questions, ethical decisions, and cost barriers. Teaching medical students from the start of medical school to handle multiple variables is an important aspect of their learning. Studies indicate that PBL students consistently score at or above the national average on board exams compared to their peers. Furthermore, evaluations of competence during clinical rotations show statistically significant advantages for PBL students in areas such as critical thinking, social and cognitive interactions, and patient comfort. Studies highlight a notable advantage in interpersonal skills among PBL students. Additionally, geographical access plays a critical role in enrollment, and personal responsibilities can hinder potential applicants from pursuing medical school. PBL can be utilized to create an environment where location-based barriers are minimized to increase the number of individuals entering the medical profession. This approach could ultimately reduce the healthcare burden and enhance medical services in underserved areas of the country. Here, we present a concise review of resources and approaches including online and digital platforms to facilitate curriculum development and implementation of flipped classrooms and independent learning that are well-suited for PBL.